The Influence of Leadership And Motivation on Employee Performance In PT.PG Rajawali II Unit of Cirebon's Directors' Office - H. Ade Solahudin., (SINTESA, 2023)
This study aims to test the influence of leadership and work motivation on employee performance at PT. PG Rajawali II Unit of the Office of Directors of Cirebon. The research method used in this study is the quantitative research method. The population in this study were employees of PT. PG Rajawali II Cirebon Office Unit has 89 employees with a sample number of 89 employees. The sampling technique is nonprobability sampling using the Total Sampling Technique so that in this study samples were taken from the entire population in PT. PG Rajawali II Unit of the Office of Directors of Cirebon. The technique of data collection using questionnaires and the results of the data analysis used are multiple regression analysis. The results of the study showed partially the positive and significant influence of leadership and work motivation variables on employee performance can be seen from thitung > ttable of 15.064 > 1.98761 The positive and significant influence of leadership variables on employee performance can be seen from thitung > ttable of 21.914 > 1.98761 and simultaneously the work motivation variable has a positive and significant effect on employee performance, and the results of the test of leadership and work motivation shown in FCalculation > Ftable of 272.073 > 3.1, which means It has a positive and significant impact on employee performance